Semaphorin-4D (Sema-4D), the Plexin-B1 ligand, is involved in mouse ovary follicular development - Goldman Shlomit; Regev Avital; Shalev Eliezer (BMC, 2007)
Abstract Background Human Plexin-B1 is expressed in two truncated forms. The long form encodes a trans-membranal protein, while the short form, which is bound to the cell surface and partially secreted, possibly serves as a decoy receptor. Plexin receptors are trans-membrane proteins. The sema domain, found in the extracellular region, is common to all plexins, semaphorins, and the scatter factor receptors and is crucial for the biological activity and plexin receptor specificity. Semaphorin-4D/Plexin-B1 binding provides attractive and repulsive cues for the navigation of axonal growth cones, and new studies suggest that this system also plays a role in the regulation of the biological functions of endothelial cells, specifically in the control of angiogenesis. In a previous study, we have demonstrated the expression and possible role of Plexin-B1 in the mouse ovary. The present study was designed to test the hypothesis that Plexin-B1 effects are mediated by Semaphorin-4D. Methods In vivo expression and localization of mouse ovarian Sema-4D were tested by immunohisto-chemistry. The role of Sema-4D in follicular development was examined by in vitro growth of preantral follicles in the presence or absence of Semaphorin-4D, with or without neutralizing antibodies against Plexin-B1. Follicular growth and steroid hormone secretion rates were tested. Results Semaphorin-4D is expressed in the mouse ovary in vivo mostly in the granulosa cells and and its expression is modulated by PMSG and hCG. In the presence of Semaphorin-4D, in-vitro constant growth was observed as indicated by follicular diameter during the culture period and elevated steroid hormone secretion rates compared with control. These effects were abolished after addition of neutralizing antibodies against Plexin-B1. Conclusion In the ovarian follicle, the effect of Plexin-B1 is mediated by sema-4D.